Performans Ayam Broiler Dengan Penambahan Kefir Sebagai Probiotik - Fanani, Anhar Faisal; Fajrih, Nurul; Anjani, Fandini Meilia; Ardiansyah, A; Qulubi, M. Hadziq (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
Kefir is a fermented milk product made by inoculating milk with kefir grains, a combination of bacteria and yeast. These microorganisms will play a role in the fermentation of lactic acid and alcohol, which can provide a therapeutic effect. The presence of probiotics in feed can increase enzymatic and digestive activity. As a natural probiotic, Kefir contains various strains of bacteria and yeast that can be used as a substitute for antibiotics that are limited in their use nowadays. The effectiveness of kefir as a probiotic was studied on the production, feed efficiency, and relative weight of the digestive tract in broiler chickens. This study used DOC broiler strain MB 202 with as many as 200 unsexing using a completely random design with four treatments and five replicates for five weeks. Treatment consisted of T0 = basal ration (control), T1 = basal ration + 1.5% probiotic kefir, T2 = basal ration + 3% probiotic kefir, T3 = basal ration+ 4.5% probiotic kefir. The kefir used comes from goat's milk which was given as much as 10% grain kefir fermented for 48 hours. The ANOVA resulted from a real difference (P<0.05) in performance for each treatment compared to the control. At the same time, the intestinal weight parameters of the digestive tract did not show a real difference (P>0.05). The addition of 4.5% probiotic kefir showed the best results on four performance parameters, including consumption, weight gain, and feed conversion ratio, which is also supported by the highest carcass yield compared to other treatments.